Fast figuring of large optics by reactive atom plasma - Castelli, Marco; Jourdain, Renaud; Morantz, Paul; Shore, Paul (Cranfield University, 2012)
The next generation of ground-based astronomical observatories will require fabrication and maintenance of extremely large segmented mirrors tens of meters in diameter. At present, the large production of segments required by projects like E-ELT and TMT poses time frames and costs feasibility questions. This is principally due to a bottleneck stage in the optical fabrication chain: the final figuring step. State-of-the-art figure correction techniques, so far, have failed to meet the needs of the astronomical community for mass production of large, ultra-precise optical surfaces. In this context, Reactive Atom Plasma (RAP) is proposed as a candidate figuring process that combines nanometer level accuracy with high material removal rates. RAP is a form of plasma enhanced chemical etching at atmospheric pressure based on Inductively Coupled Plasma technology. The rapid figuring capability of the RAP process has already been proven on medium sized optical surfaces made of silicon based materials. In this paper, the figure correction of a 3 meters radius of curvature, 400 mm diameter spherical ULE mirror is presented. This work demonstrates the large scale figuring capability of the Reactive Atom Plasma process. The figuring is carried out by applying an in-house developed procedure that promotes rapid convergence. A 2.3 μm p-v initial figure error is removed within three iterations, for a total processing time of 2.5 hours. The same surface is then re-polished and the residual error corrected again down to& lambda;/20 nm rms. These results highlight the possibility of figuring a metre-class mirror in about ten hours.
Keywords: Large optical components, figuring, tool-path algorithms, plasma etching, optical fabrication, extremely large telescopes.